Advances in immunotherapy modalities for atherosclerosis - Qingwen Meng; Qingwen Meng; Qingwen Meng; Huajiang Liu; Jinteng Liu; Yangyang Pang; Qibing Liu; Qibing Liu (Frontiers Media S.A., 2023)
Cardiovascular disease (CVD) is one of the leading causes of death worldwide. Atherosclerosis is the pathological basis of atherosclerotic cardiovascular disease (ASCVD). Atherosclerosis is now understood to be a long-term immune-mediated inflammatory condition brought on by a complicated chain of factors, including endothelial dysfunction, lipid deposits in the artery wall, and monocyte-derived macrophage infiltration, in which both innate immunity and adaptive immunity play an indispensable role. Recent studies have shown that atherosclerosis can be alleviated by inducing a protective immune response through certain auto-antigens or exogenous antigens. Some clinical trials have also demonstrated that atherosclerotic is associated with the presence of immune cells and immune factors in the body. Therefore, immunotherapy is expected to be a new preventive and curative measure for atherosclerosis. In this review, we provide a summary overview of recent progress in the research of immune mechanisms of atherosclerosis and targeted therapeutic pathways.